Genetic screening of THAP1 in primary dystonia patients of India. (10th January 2017) - Giri, Subhajit; Naiya, Tufan; Equbal, Zaffar; Sankhla, Charulata Savant; Das, Shyamal Kumar; Ray, Kunal; Ray, Jharna
Highlights: Indian primary dystonia patients with THAP1 variants are clinically heterogeneous. Three potential THAP1 mutations were identified in three patients. These patients demonstrate cervical involvement with tremor and speech problems. Among two SNPs detected in patients and controls one might pose risk to patients. Abstract: Background: Primary Dystonia is a common movement disorder manifested by dystonic symptoms only. DYT6, a major genetic factor, plays a significant role in primary pure dystonia pathogenesis. In this study we analyzed THAP1 (DYT 6) gene in primary pure dystonia patients, which has been widely studied in other populations but not in Indians. Methods: The study cohort contained 227 index primary pure dystonia patients with the involvement of cervical region and 254 neurologically control individuals collected from East Indian population. All three exons of THAP1 and their flanking sequences, including exon-intron boundaries, were screened by PCR, DNA sequencing and/or RFLP analysis. Results: A total of three nucleotide variants were detected, which include a reported missense mutation (c.427 A > G; p.Met143Val) in a juvenile onset generalized dystonia patient, a novel frameshift deletion mutation (c.208-209 ΔAA; p.K70VfsX15) in a juvenile onset cervical dystonia patient and a rare variant in 3′ UTR of THAP1 (c.*157 T > C) in an adult-onset blepharospasm patient. In addition, two SNPs (rs71521601 and rs111989331) were detected both in the patients and controls with the major allele of the latter being significantly over represented in the patients. Conclusions: Our study suggests that the THAP1 is likely to have a causative role in the pathogenesis of Indian primary pure dystonia patients. Though the phenotypic spectrum is extensively diverse, the cervical involvement with dystonic tremor and speech problem is common amongst the patients harboring mutations.